Audit delay, corporate operational complexity, and Computer-Assisted Audit Techniques (CAATs) - Iryani, Lia Dahlia; Farida, Ida; Rosanti, Sri; Maulida, Syahdatul (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This study analyzes the impact of corporate profitability, corporate leverage, firm size, firm age, and the use of Computer-Assisted Audit Tools (CAATs) on audit delay. The study highlights the importance of auditors’ digital readiness in managing corporate operational complexity. The applied method is a panel data regression analysis using Eviews 13 software. The sample consisted of 20 companies audited by KAP BAMS from 2020 to 2022. The results show that all independent variables have a significant effect on audit delay. However, on a partial basis, profitability, leverage, and CAATs variables do not show significant impact. In contrast, firm size and firm age have been found to significantly influence audit delay. A notable insight emerges as CAATs, expected to expedite the audit process are instead positively associated with longer delays. This underscores the gap between technology adoption and auditor competence in practice. This study contributes to the literature by emphasizing that audit technology is only effective when supported by user readiness and adequate digital infrastructure. The implications of these findings suggest that companies and auditors should pay particular attention to firm size, firm age, and the utilization of CAATs to minimize audit delays.